Analyzing the Role of Beauty Classes and Beauty Events as Below the Line (BTL) Promotional Strategies in Enhancing Brand Awareness at PT - Gunawan, Ath Thariq Athrizqullah; Nugroho, Rusdi Hidayat (CV. Lenggogeni Data Publishing, 2024)
This study aims to analyze the role of beauty classes and beauty events as Below the Line (BTL) promotional strategies at PT Vitapharm (Viva Cosmetics) in enhancing brand awareness among consumers. A qualitative approach was employed, utilizing direct observations and in-depth interviews with participants of beauty classes and beauty events, alongside marketing managers at PT Vitapharm. Data collection focused on evaluating the effectiveness of these strategies in raising consumer brand awareness. Thematic analysis was conducted to identify key insights and recurring patterns in participant experiences and perceptions. The findings reveal that beauty classes and beauty events significantly enhance brand awareness. Participants reported improved familiarity with the brand and its product offerings, as well as stronger emotional connections with Viva Cosmetics. The interactive and experiential nature of these events fosters deeper consumer engagement and promotes brand recognition. The study also highlights the importance of experiential marketing in strengthening brand visibility within the competitive cosmetics industry. This research concludes that beauty classes and beauty events serve as effective BTL promotional strategies for PT Vitapharm (Viva Cosmetics). By delivering engaging and informative consumer experiences, these activities strengthen the brand's presence and recognition in the market. Future studies could investigate the scalability of such strategies and their long-term impacts on brand.